2006
DOI: 10.1093/annonc/mdj111
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of familial Waldenström's macroglobulinemia

Abstract: The above results suggest a high degree of clustering for B-cell disorders among first-degree relatives of patients with WM, along with distinct clinical features at presentation based on familial disease cluster patterns. Genomic studies to delineate genetic predisposition to WM are underway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
96
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(99 citation statements)
references
References 31 publications
3
96
0
Order By: Relevance
“…8 A number of affected families presenting multiple cases, as well as case-control and cohort studies, have been published showing familial clustering of LPL and WM. [9][10][11][12][13] Recently, based on data from a referral clinic with particular focus on familial disease, Treon et al reported that 19% of their WM patients had at least one first-degree relative affected with WM or another B-cell disorder. 13 To quantify risk estimates for familial aggregation in the general population, we recently performed a large population-based study, including 2,144 LPL/WM patients, 8,279 population-based matched controls, and linkable first-degree relatives of patients (n=6,177) and controls (n=24,609).…”
Section: Lymphomasmentioning
confidence: 99%
See 1 more Smart Citation
“…8 A number of affected families presenting multiple cases, as well as case-control and cohort studies, have been published showing familial clustering of LPL and WM. [9][10][11][12][13] Recently, based on data from a referral clinic with particular focus on familial disease, Treon et al reported that 19% of their WM patients had at least one first-degree relative affected with WM or another B-cell disorder. 13 To quantify risk estimates for familial aggregation in the general population, we recently performed a large population-based study, including 2,144 LPL/WM patients, 8,279 population-based matched controls, and linkable first-degree relatives of patients (n=6,177) and controls (n=24,609).…”
Section: Lymphomasmentioning
confidence: 99%
“…[9][10][11][12][13] Recently, based on data from a referral clinic with particular focus on familial disease, Treon et al reported that 19% of their WM patients had at least one first-degree relative affected with WM or another B-cell disorder. 13 To quantify risk estimates for familial aggregation in the general population, we recently performed a large population-based study, including 2,144 LPL/WM patients, 8,279 population-based matched controls, and linkable first-degree relatives of patients (n=6,177) and controls (n=24,609). 14 We found first-degree relatives of LPL/WM patients had a significantly increased risk of developing LPL/WM, other subtypes of NHL (including CLL), and MGUS, compared to first-degree relatives of controls, with the highest risk for LPL/WM (Table 1).…”
Section: Lymphomasmentioning
confidence: 99%
“…[43][44][45][46] Some patients have cellular infiltration at the pulmonary parenchymal level, 47,48 being coughing the most common symptom, followed by dyspnea and chest pain. Renal infiltration has also been reported, 49 as well as cutaneous infiltration (maculopapular lesions, plaques or nodules) 7,50 and infiltration of periorbital structures, such as the tear gland and retro-orbital lymphoid tissue (ocular tremors). 51,52 The infiltration of malignant cells in the central nervous system is responsible for a rare neurological disorder called Bing-Neel syndrome.…”
Section: Clinical Symptomsmentioning
confidence: 99%
“…5 In relation to familial predisposition, an association is estimated in 20% of cases. 6,7 In first degree family relations there is a high risk of developing lymphoproliferative diseases, which is twenty times higher for WM/LPL. 8 pathophySIology It is believed that WM originates in memory B-lymphocytes.…”
mentioning
confidence: 99%
“…Waldenstro¨m's macroglobulinemia (WM) is a B-cell malignancy characterized by the underlying pathological diagnosis of lymphoplasmacytic lymphoma using REAL or WHO criteria and the presence of IgM monoclonal gammopathy [1]. While a familial predisposition may exist in up to 20% of patients with WM, a precipitating cause remains unknown for most patients [2].…”
Section: Introductionmentioning
confidence: 99%